2010
DOI: 10.1111/j.1440-1827.2010.02518.x
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing sialometaplasia of the parotid gland associated with angiocentric T‐cell lymphoma: A case report and review of the Literature

Abstract: A very rare case of necrotizing sialometaplasia of the parotid gland associated with angiocentric T-cell lymphoma was described. A 66-year-old male had left neck and pharyngeal masses and biopsy specimen showed a monotonous proliferation of atypical lymphoid cells with massive necrosis in the parotid gland. Angiocentric pattern or vascular invasion by the lymphoid cells was observed and the involved parotid gland exhibited squamous metaplasia of the ducts and acini; necrotizing sialometaplasia. Immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…La SMN peut survenir sur un terrain vasculaire : une athé-rosclérose [8], une hypertension artérielle [8][9][10][11][12][13][14][15][16], une maladie de Buerger [17]. Dans d'autres cas, un facteur traumatique (physique, chimique, thermique…) précédant la survenue de la SMN a été retrouvé : injections d'anesthésiques locaux et usage de produits chimiques lors des soins dentaires [15,[17][18][19][20][21][22][23], ingestion de boissons chaudes [24], port de prothèses dentaires [3, 8-11, 18, 21, 23, 25-39], intervention chirurgicale loco-régionale [18][19][20][21][22][23][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Théorie Vasculaireunclassified
See 2 more Smart Citations
“…La SMN peut survenir sur un terrain vasculaire : une athé-rosclérose [8], une hypertension artérielle [8][9][10][11][12][13][14][15][16], une maladie de Buerger [17]. Dans d'autres cas, un facteur traumatique (physique, chimique, thermique…) précédant la survenue de la SMN a été retrouvé : injections d'anesthésiques locaux et usage de produits chimiques lors des soins dentaires [15,[17][18][19][20][21][22][23], ingestion de boissons chaudes [24], port de prothèses dentaires [3, 8-11, 18, 21, 23, 25-39], intervention chirurgicale loco-régionale [18][19][20][21][22][23][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Théorie Vasculaireunclassified
“…64 % des cas de SMN étaient associés à une lésion tumorale bénigne ou maligne [16,28,42,43,46] ; la lésion pouvait également être la consé-quence d'une sialadénite lobulaire focale [118].…”
Section: Smn Des Glandes Salivaires Accessoiresunclassified
See 1 more Smart Citation
“…The clinical presentation in conjunction with some features of the histological characteristics may lead to the erroneous diagnosis of malignancy. Moreover, NS has been reported in conjunction with both benign (Giunchi and Bulatao, 2012) and malignant tumors (Lee et al, 2009;Ravn et al, 2009;Yoshioka et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking, chronic alcohol use, unsuitable dentures, local anesthesia, surgical treatment, external wounds, upper respiratory infections, tumors, operations, irradiation and frequent emesis are thought to be local causes of NS (2,8,(23)(24)(25)(26). Dominguez-Malagon et al (24) and Yoshioka et al (25) reported that T-cell lymphoma is considered as a causative condition of NS. Ylikontiola et al reported that a girl's adenoidectomy may have affected branches of the palatine arteries in the soft palate, compromised the underlying vascular supply and likely caused infarction of the salivary gland tissue (26).…”
Section: Discussionmentioning
confidence: 99%